ANALISIS KESALAHAN BERBAHASA DALAM SKRIPSI MAHASISWA PGMI PTI AL-HILAL SIGLI - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
The aim of the study was to find out the incorrect writing forms which do not officially fit to the standard rule of Indonesian language and the form of scientific writing. The method used was Evaluative. The researcher took five theses as the data source in this study. Each thesis was analysed precisely. The findings came up with some incorrectness in theses-writing which did not suit the standardrule of Indonesian language. Most of writers composed such long-ambigous sentences. Furthermore, they also ignored the right use of punctuations and conjunctions. As a result, sentences werenot coherent and not understandable.